2008
DOI: 10.1063/1.2975165
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid green light-emitting diode comprised of n-ZnO/(InGaN/GaN) multi-quantum-wells/p-GaN

Abstract: Hybrid green light-emitting diodes (LEDs) comprised of n-ZnO/(InGaN/GaN) multi-quantum-wells/p-GaN were grown on semi-insulating AlN/sapphire using pulsed laser deposition for the n-ZnO and metal organic chemical vapor deposition for the other layers. X-ray diffraction revealed that high crystallographic quality was preserved after the n-ZnO growth. LEDs showed a turn-on voltage of 2.5 V and a room temperature electroluminescence (EL) centered at 510 nm. A blueshift and narrowing of the EL peak with increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 18 publications
3
37
0
Order By: Relevance
“…The blue-shift has been attributed to several different factors, such as band renormalization and band filling [383], and the screening effect of the built-in [371]. Reproduced with permission piezoelectric field [384].…”
Section: Inorganic Heterojunction Ledsmentioning
confidence: 99%
“…The blue-shift has been attributed to several different factors, such as band renormalization and band filling [383], and the screening effect of the built-in [371]. Reproduced with permission piezoelectric field [384].…”
Section: Inorganic Heterojunction Ledsmentioning
confidence: 99%
“…Obtained results indicate that all the emission peaks (orange, yellow, blue under reverse bias, and violet under forward bias), originate from the p-GaN layer and/or GaN/ZnO interface since they can be observed in the absence of ZnO, as discussed in the Subsection III D. To improve the brightness of the devices, we have utilized a simple approach of growing ZnO nanostructures on a commercial group-III nitride-based LED wafer. 10,30 It has been shown that device architectures containing ZnO and InGaN multiple quantum wells (MQWs), [31][32][33] where dominant light emission peak originates from InGaN MQW, [31][32][33] can result in bright devices with low turn-on voltage (2.5 V). 31,32 Thus, we have employed a simple method of growing ZnO nanorods by electrodeposition on top of a commercial, unetched GaN-based LED wafer followed by the deposition of electrode onto ZnO, without any etching steps involved.…”
Section: Introductionmentioning
confidence: 99%
“…10,30 It has been shown that device architectures containing ZnO and InGaN multiple quantum wells (MQWs), [31][32][33] where dominant light emission peak originates from InGaN MQW, [31][32][33] can result in bright devices with low turn-on voltage (2.5 V). 31,32 Thus, we have employed a simple method of growing ZnO nanorods by electrodeposition on top of a commercial, unetched GaN-based LED wafer followed by the deposition of electrode onto ZnO, without any etching steps involved. Using such a simple process, high brightness devices have been achieved, as discussed in Subsection III E.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Other promising optoelectronic device applications include blue and green light emitting diodes, [5][6][7] where ZnO can be used either as the active region or as a transparent contact.…”
mentioning
confidence: 99%